KONVERGENSI IFRS, KUALITAS AUDIT, DAN MANAJEMEN LABA - Fitri Ramadhani; Theresia Woro Damayanti (Akutansi Bisnis & Manajemen ( ABM ), 2020)
The purpose of this study is to analyzed how the IFRS convergence influence earnings management with audit quality as a moderating variable. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange in the period 2008-2018 obtained using the purposive sampling method. The results of the study using panel data analysis showed that IFRS convergence negatively and significantly affected earnings management.This shows that the convergence of IFRS has an impact on the decline in earnings management practices. However, this study failed to prove audit quality as a moderating variable.